Chemoradiotherapy in a Case of Malignant Syringocystadenocarcinoma Papilliferum of Vulva with Locoregional Failure - Pamidimukkala Bramhananda Rao; Saptarshi Ghosh; Manisha Mohapatra; N. Pramod Philip; P. Ravindra Kumar; Surendra Manam; Pradeep Karra; Vijay Krishna Jasti (Case Reports in Oncological Medicine)
Introduction. Syringocystadenocarcinoma papilliferum (SCACP) is an extremely rare malignant adnexal tumor, which arises from syringocystadenoma papilliferum. To date, less than 30 cases of malignant SCACP have been reported, of which locoregional metastases were found in only four cases. Case Report. A 57-year-old female patient who presented to our Oncology Department with a recurrent malignant SCACP of the left labia along with right inguinal lymphadenopathy. Pathological examination confirmed the diagnosis of malignant SCACP with right inguinal lymph node metastases. Due to the fixity of the right inguinal nodes, neoadjuvant chemotherapy was administered with Cisplatin and 5-Fluorouracil for four cycles, following which the primary tumor and the contralateral inguinal nodes regressed completely. Then definitive chemoradiation was delivered with five cycles of weekly Cisplatin and external beam pelvic irradiation up to a dose of 59.4 Gy. Patient is disease-free 11 months after treatment. Discussion. We here report the fifth case of malignant SCACP with locoregional metastases. This is the first case of malignant SCACP which has been treated with neoadjuvant chemotherapy followed by concurrent chemoradiation. Although surgery has been used most commonly, chemoradiation may also have a role in the treatment of malignant SCACP, especially in cases of locoregional metastases.